PENENTUAN MUTU BRIKET BIOARANG DARI BAHAN BAKU LIDI IJUK DAN SERUTAN KAYU * - Gebbi Y. Ngajow; Daniel P.M. Ludong; Freeke Pangkerego; Ruland A. Rantung (COCOS, 2016)
ABSTRACTThis study aimed to evaluate the briquet quality made of palm leaf-rib from sugar palm plant and wood shavings based on the water content, ash content and briquet burning capacity as well as to determine the best quality of briquet based on the water and ash content.The results of this descriptive study showed that the highest water content was observed in the palm leaf-rib briquet (12,68 %) and the lowest was in the briquet made of 66,67 % palm leaf-rib and 33,33 % wood shavings (2,58 %). The highest ash content was in the briquet made of 100 % wood shavingsKeywords ; briquet, palm leaf-rib, sugar palm plant, wood shavings, quality